Penerapan Metode Picture to Picture Mata Pelajaran Bahasa Indonesia Pada Siswa SDN Jatirasa III Bekasi - Lengsi Manurung (Peneliti.net, 2019)
The purpose of this study was to describe the effectiveness of the Picture to picture method in Indonesian subjects, at Al Ikhlas High School students in Bekasi. The research method used is classroom action research (action research). The activity consists of 3 stages. The first stage is carried out pre-cycle, the second stage is carried out after the pre-cycle. In the third stage, it is hoped that the class action process can determine the target of learning outcomes in accordance with the criteria for material completeness. The object of the research is the students of SD Jatirasa III, Bekasi city. The students who participated in the research were 25 grade 5 students. The results showed that the pre-cycle value. The value of cycle 1 is 69 and the value of cycle 2 is 76, there is an increase of 7 points. Suggestions for teachers can use this as a reference method. Besides, it can be the basis for further research.